Triterpene Structural Diversification by Plant Cytochrome P450 Enzymes - Ghosh, Sumit (Frontiers in Plant Science, 2017)
Cytochrome P450 monooxygenases (P450s) represent the largest enzyme family of the plant metabolism. Plants typically devote about 1% of the protein-coding genes for the P450s to execute primary metabolism and also to perform species-specific specialized functions including metabolism of the triterpenes, isoprene-derived 30-carbon compounds. Triterpenes constitute a large and structurally diverse class of natural products with various industrial and pharmaceutical applications. P450-catalyzed structural modification is crucial for the diversification and functionalization of the triterpene scaffolds. In recent times, a remarkable progress has been made in understanding the function of the P450s in plant triterpene metabolism. So far, ~80 P450s are assigned biochemical functions related to the plant triterpene metabolism. The members of the subfamilies CYP51G, CYP85A, CYP90B-D, CYP710A, CYP724B and CYP734A are generally conserved across the plant kingdom to take part in plant primary metabolism related to the biosynthesis of essential sterols and steroid hormones. However, the members of the subfamilies CYP51H, CYP71A,D, CYP72A, CYP81Q, CYP87D, CYP88D,L, CYP93E, CYP705A, CYP708A and CYP716A,C,E,S,U,Y are required for the metabolism of the specialized triterpenes that might perform species-specific functions including chemical defense towards specialized pathogens. Moreover, a recent advancement in high-throughput sequencing of the transcriptomes and genomes has resulted in identification of a large number of candidate P450s from diverse plant species. Assigning biochemical functions to these P450s will be of interest to extend our knowledge on triterpene metabolism in diverse plant species and also for the sustainable production of valuable phytochemicals.